A Theory-Based Intervention in Health Visiting Students in Order to Reduce Mental Illness Stigma: A Quasi-Experimental Study - Georgia Koutsouradi; Christina Dimitrakaki; Eirini Agapidaki; Yannis Tountas; Areti Lagiou (Archives of Community Medicine and Public Health - Peertechz Publications, 2016)
Background: Stigma of mental illness is an important barrier to treatment and recovery of mental illness. Schizophrenia represents the most common mental disorder for the public and it is connected with the highest stigma due to misconceptions of dangerousness. Stigmatizing attitudes have been found not only among general population but also in health care providers. Objectives: A randomized trial was conducted in order to evaluate a short duration theory-based intervention programme to reduce potential stigma of mental illness, specifically schizophrenia, in a sample of Health Visiting students. The intervention involved education combined with video based contact with people with mental illness; this specific intervention scheme has proved to be the most effective intervention strategy and has been proposed as a good practice for stigma reduction. Methods: In 2015, fifty seven Health Visiting students of the Athens Technological Education Institute who accepted to participate in the research were randomly assigned in two groups: an intervention group which received education and video-based contact with people with experience of mental illness and a control group which received education but no contact. The Mental Health Knowledge Scale (MAKS), the Attitudes to Severe Mental Illness (ASMI) Scale and the Social Distance Scale (SDS) were used to evaluate students' knowledge, attitudes and desired social distance from people with schizophrenia respectively, at three points of time (pre, mid, post). Results: Although no cut-off points exist for any of the scales, health visiting students were found to hold relatively positive attitudes towards mental illness. As expected, stigma-related mental health knowledge increased in both groups after the intervention. The intervention group also improved their scores on the factor "Optimism" of the ASMI scale and decreased their stigma scores on the factor "Close Relations" of the SCD scale. Conclusions: Our results indicate that stigma-related mental health knowledge can b  increased with a short duration intervention, whilst negative attitudes and increased desired social distance from people with mental illness are more resistant to change. Further research is needed to explore the specific  omponents